CORRELATION OF KNOWLEDGE LEVEL OF PROSPECTIVE CIVIL SERVANTS TO THE COMMUNICATION OF THE DIFFUSION OF INNOVATIONS WITH THE BLENDED LEARNING METHOD IN TANAH LAUT DISTRICT - Bornea Retno Mahalayati; Sanusi Sanusi (Universitas Lambung Mangkurat, 2022)
The COVID-19 pandemic has caused big-scale changes, especially related to society’s mobility. Many big events caused big masses to be delayed or even worst canceled, including the basic training for prospective civil servants of Tanah Laut district Formation in 2019. The government then came up with a solution to use the innovation known as the blended learning method. This research aims to find out whether the use of the blended learning method correlates with the civil servant candidates’ knowledge and literacy level and even on the basic training for prospective civil servants of Tanah Laut district Formation in 2019 itself. This research is quantitative research using the correlation method. The subject of this study is the entire population consisting of 172 people. They were asked to fill out a questionnaire shared through Google Docs. For data analysis, the researcher used classical assumption tests. Then for the hypothesis test, researchers use the t-test and also the determination coefficient test. Based on the results of the t-test, it is known that the diffusion of blended learning method innovation correlates with the improvement of the participant's knowledge level. Furthermore, this method is effective to improve participants’ literacy levels due to the use of the internet as a learning source. The last, the use of the blended learning method is considered effective and efficient in basic training for prospective civil servants of Tanah Laut district Formation in 2019 because the learning process feels more flexible.